2016
DOI: 10.1159/000450707
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathological Course Typology in Schizophrenia Spectrum Disorders: A Heuristic Approach in a Sample of 100 Patients

Abstract: Background: Despite several previous attempts at subtyping schizophrenia, a typology that reflects neurobiological knowledge and reliably predicts course and outcome is lacking. We applied the system-specific concept of the Bern Psychopathology Scale (BPS) to generate a course typology based on three domains: language, affectivity, and motor behaviour. Sampling and Methods: A cohort of 100 patients with schizophrenia or schizoaffective disorders according to DSM-IV criteria underwent psychopathological assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 31 publications
(55 reference statements)
1
6
0
2
Order By: Relevance
“…The BPS [6] is a tool that follows such an approach. It is complementary to the positive-negative approach [15] and related to global functioning [19] as well as severe clinical events [20] and has been used to retrospectively describe the course of schizophrenia [16]. Previously, a prospective application of the BPS in a cohort of patients with schizophrenia had been lacking, and to our knowledge, this is the first study to apply such an approach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The BPS [6] is a tool that follows such an approach. It is complementary to the positive-negative approach [15] and related to global functioning [19] as well as severe clinical events [20] and has been used to retrospectively describe the course of schizophrenia [16]. Previously, a prospective application of the BPS in a cohort of patients with schizophrenia had been lacking, and to our knowledge, this is the first study to apply such an approach.…”
Section: Discussionmentioning
confidence: 99%
“…Both the PANSS and BPS were designed as instruments for cross-sectional assessment, but our group has used the BPS to categorise longitudinal data retrospectively [16]. In this retrospective study, we found that 86% of patients showed a bipolar course pattern (i.e., they showed switches from inhibition to disinhibition or vice versa) in at least 1 of the 3 domains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it allows recurrent assessments at deliberate intervals for follow-up observations. First retrospective studies have recently been published [7], and the issue of the course of psychosis dimensions will be addressed in detail in future projects.Regarding negative symptoms, we pursued a novel approach, mapping "negative" behavior onto inhibitory states of the respective brain functions. Following our objective to revise the semiology of psychosis based on the best of our knowledge about the related brain functions, this group of symptoms was disentangled respecting the boundaries of higher brain functions.…”
mentioning
confidence: 99%
“…However, it allows recurrent assessments at deliberate intervals for follow-up observations. First retrospective studies have recently been published [7], and the issue of the course of psychosis dimensions will be addressed in detail in future projects.…”
mentioning
confidence: 99%